Role of Panchmahabhautik Siddhanta in the Ayurvedic Approach to Hypothyroidism - Dr. Palakkumari Paramar; Prof. (Dr.) Naresh Kore (The Bioscan, 2026)
Hypothyroidism is a common endocrine disorder characterized by inadequate thyroid hormone production, resulting in hypometabolic manifestations such as weight gain, fatigue, constipation, and myxoedema. In modern medicine, its main causes include iodine deficiency, autoimmune thyroiditis, and surgical interventions, whereas in Ayurveda, similar symptomatology is associated with Galganda, Pāṇḍu, Sopha, and Atisthāulya, arising from Rasadhātu duṣṭi, Agnimandya, and vitiation of Kapha and Vāta doṣas.